Design Prototype of Simple Jarimatic Visualization Application Model, Attracting, Motivating Early Children to Learn and Grow - Ekowati, Maria Atik Sunarti (Research Collaboration Community (Rescollacom), 2022)
The main purpose of this work is to develop a model or product design into a final product that can meet user demands. The methodology of this study is the product development by making designs, samples, or models with the aim of testing the concept or work process of the product. In the product development process, users can take part in the product development process by evaluating and providing feedback. Therefore, we create a prototype design for a simple, attractive, and attractive Jarimatika visualization application model that motivates early childhood to learn and grow, which results in a product development of the Jarimatika Visualization Software.